Rescuers at Risk: Posttraumatic Stress Symptoms Among Police Officers, Fire Fighters, Ambulance Personnel, and Emergency and Psychiatric Nurses - Soravia, Leila M.; Schwab, Simon; Walther, Sebastian; Müller, Thomas (Frontiers in Psychiatry, 2021)
Emergency personnel and rescue workers may be at a risk of posttraumatic stress symptoms (PTSS) due to exposure to trauma and work-related stressors. Though rescuers of different professions are often engaged in the same type of emergency, they have different tasks and responsibilities and receive different training in coping with traumatic events and stress; hence, we speculated that the salience of identified risk factors for PTSS vary across their respective professions. The present cross-sectional survey aimed to identify influencing variables on PTSS, well-being, and suicidal ideation that can act differently across professions of rescue workers and emergency personnel. In this anonymous online study, data from 1,002 rescue workers and emergency personnel in Switzerland, were collected: 499 police officers, 239 firefighters, 97 ambulance personnel, and 85 emergency and 82 psychiatric nurses. PTSS, coping strategies, well-being, suicidal ideation, previously experienced and work-related trauma and self-efficacy were measured and analyzed using multiple regression and structural equation modeling (SEM). The prevalence of suspected posttraumatic stress disorder varied across the professions, ranged from 8% (firefighters) to 22% (psychiatric nurses), and was associated with psychological strain and suicidal ideation. The SEM showed that dysfunctional coping strategies, self-efficacy, previously experienced and work-related trauma, years on job, and female sex explained up to 78% of PTSS and that PTSS itself explained up to 68% of the psychological strain experienced in the different professions. Independent of the profession, dysfunctional coping such as alcohol use, avoidance, and distraction, as well as work-related trauma were the most robust predictors of PTSS. However, while self-efficacy was a risk factor for police officers, firefighters and ambulance personnel, it was a protective factor for emergency and psychiatric nurses. Furthermore, female sex was only a risk factor for ambulance personnel and emergency nurses. In agreement with prior research, emergency personnel and rescuers exhibited enhanced prevalence of PTSS and suspected PTSD, leading to significant psychological strain and suicidal ideation. However, risk factors varied across the professions. Thus, the development of profession-specific trainings to improve self-efficacy and coping with work-related stressors to reduce PTSS, and enhance quality of life, is needed for individuals in such high-risk professions.